Strong etching investigation on PADC CR-39 as a thick track membrane with deep depth profile study. (December 2020) - Awad, E.M.; Hassan, Sameh; Bebers, Eman; Rammah, Y.S.
Abstract: Shape and size of micro-tubes produced by high energy Au, Ni, Si and Fe ions on thick CR-39 polymer processed in strong etching solution were studied. Deep internal polymer track parameters of sensitivity (V); bulk (Vb ) and track etch rates (Vt ) were intensively investigated by measuring the track opening as well as the track cone length. Development of track envelope with etching was studied using track profile technique, TPT. Variations in Vb, Vt, and V with deep depth inside the polymer were studied down to ≈100 μm depth or more. CR-39 sensitivity was reduced to 60–70% at the first 25 μm inwards. Microphotographs for the developed track profile for each ion was shown. Fe and Si profiles show new and interesting track profile for the first time where their profiles deviate from the normal cone shape of the track. Ion's track membranes (TMs) for thick CR-39 polymer were produced and their properties were determined. Highlights: CR-39 deep depth profile and response study. High energy ions track profile. New Fe cone profile. New Si cone profile. Thick nuclear track membranes, TMs.